Special education need the true leadership: the review - Ibrahim, Badaruddin; Nordin, Mohd Norazmi; Mustafa, Mohamad Zaid; Abdul Razzaq, Abdul Rasid (Türkiye Fizyoterapistler Derneği, 2021)
Special education leadership is an aspect of comprehensive management related to special education operations that includes knowledge, leadership style and also the welfare of teachers and students. Good leadership for a special education program should implement the process of planning, organizing, directing and controlling the members of the organization as well as using all organizational resources to achieve specific goals for special education. The leadership practiced in special education needs to make the special education program improve and be able to carry out its functions properly. This survey was conducted to evaluate the existing leadership theories in determining the right options for practice in special education.